Time-domain and frequency-domain effects of tensor tympani contraction on middle ear sound transmission in gerbil - Gallagher, Liam (Hear Res, 2021)
The middle ear is a high-fidelity, broadband impedance transformer that transmits acoustic stimuli at the eardrum to the inner ear. It is home to the two smallest muscles in mammalian species, which modulate middle ear transmission. Of this pair, the function of the tensor tympani muscle (TTM) has remained obscure. We investigated the acoustic effects of this muscle in young adult gerbils. We measured changes in middle ear vibration produced by pulse-train-elicited TTM contraction – in the time-domain with a click stimulus and in the frequency-domain with multitone zwuis stimuli. In our click experiments, there was generally a small reduction in the primary peak of the response and a slight increase in the subsequent ringing, but there was essentially no change in the delay of the click response at the umbo (less than 1 μs change). In our multitone experiments, there were consistent patterns of attenuation and enhancement in the velocity responses at the umbo and ossicles. TTM contraction produced a narrow band of enhancement around 6 kHz (maximally ~5dB) that can be modeled with an increased stiffness of an overdamped spring-mass resonance. At frequencies below 2 kHz and above 35 kHz, TTM contraction attenuated middle ear vibrations by as much as fivefold.